“Aspectos Motivacionales De 21 Catequistas Voluntarios” (2015)
This research project focuses on the description of the motivational aspects in 21 volunteer catechists two parishes: Nuestra Señora del Ave María y Santa María de NazaretHail Mary and Our Lady of Nazareth. A review of research was carried out previously made regarding the motivation of individuals who volunteer in the Colombian context and studies of different careers but little participation of psychology found, for this reason the most important studies were presented during the written They were instrumental in the time of analysis of results achieved after applying the instrument called volunteer Functions Inventory indicating the dimensions in which participants generate greater motivation for performing voluntary. The dimensions are: career, understanding, improvement, protection, social, values.